Cultivation of Water Spinach (Ipomoea Reptans Poir) Production By Using Dft and Nft - Imam Safir Alwan Nurza (Journal of Social Research, 2022)
Water spinach (Ipomoea reptans Poir) is one of the horticultural crops known for its very easy cultivation and fast harvest cycle and high nutritional value. This plant can be produced or cultivated hydroponically using NFT (Nutrient Film Technique) and DFT (Deep Flow Technique) systems. Cultivation of plants in the NFT system uses a sloping circuit with shallow nutritious water that circulates for 24 hours at a fast flow. The DFT system uses a closed-circuit insulated with stagnant water that circulates for 24 hours at a slow flow. Thus, this research was conducted to determine the differences in the production of water spinach in two hydroponic systems, namely NFT and DFT. The research was conducted using a Randomized Block Design (RAK) and observation method by observing plant height, number of leaves, wet weight, and root length. Data were analyzed using independent samples T-test with a prerequisite test in the form of the Shapiro-Wilk normality test. The results of this research showed that the cultivation of water spinach using NFT and DFT hydroponic systems had significant differences in plant height, number of leaves, root length, and wet weight. Water spinach production can be increased by using DFT compared to NFT.